Educational software to achieve significant learning in mathematics - Vidaurre García, Wilmer Enrique (2015)
An educational software can be used in all school subjects and in many different ways such as: connecting, making easy to organize information, using questionnaires, etc. They provide a more attractive and interactive work environment as well. Its inclusion in mathematics has to allow recreating situations and students’ reality; and stopping making it «less abstract». Edilim it´s an easy-to-use software so teachers can create their books without any inconvenient. The interface is very simple, self-explanatory and is in Spanish. Without a doubt, creating interactive activities with EdiLIM turns out to be very simple and the students, who want to learn with tools appropriated to their age, can handle it easily. This research starts from the existing problems about the significant learning in mathematics. The students do not connect easily what the teacher teaches with any knowledge acquired previously, thus it is no longer attractive. Teachers have developed skills in ICT handling and they teach mathematics using blackboards and markets. They do not find where to put in practice what they learned or what it is for. The research objective is to show that the use of the educational software «Matema-tic» created with EdiLIM contributes to achieve significant learning in mathematics. The hypothesis is accepted, as it is formulated: The educational software Matematic application created with Edilim will achieve significant learning in mathematics with the high school students from the first grade secondary level at Santa Magdalena Sofía Barat School.